Retrospective analysis of scaphoid trapezium pyrocarbon implant intervention in STT arthritis: a 3-year follow-up study - Maria Zander; Allan Ibsen-Sörensen; Anders Nilsson; Anders Björkman (Journal of Plastic Surgery and Hand Surgery)
Aim: The purpose of this study was to evaluate clinical, patient rated and radiological outcome of the scaphoid trapezium pyrocarbon implant (STPI) at a minimum of three years follow-up.